Impact of COVID-19 Pandemic on Physical Activity and Energy Expenditure (European journal of volunteering and community-based projects, 2022)
Objective: The study was primarily conducted to find out the impact of COVID-19 pandemic on physical activity and energy expenditure among physiotherapy professionals and students. Design and setting: A cross sectional study was conducted across various institutes of Karachi, Pakistan. Subjects: Physical therapy students (n=264), and Physiotherapy Professionals (n=40). Tool: The International Physical Activity Questionnaire- Short Form (IPAQ-SF) was used to evaluate levels of physical activity and energy expenditure before and during COVID-19 pandemic. Results: Out of 420 surveys sent out, 308 surveys were returned showing response rate of 73%.  The total physical activity was decreased (-28%) during pandemic (2136.8 MET-min/wk) as compared to physical activity before COVID-19 pandemic (3005 MET-min/wk). Also, the energy expenditure was decreased (-28.9%) during the pandemic (4151.6 MET-min/wk) as compared to before COVID-19 Pandemic (5831.4 MET-min/wk). Conclusion: A significant reduction in physical activity and energy expenditure was reported from physiotherapy professionals and students during COVID-19 pandemic.